1933 Ohio Acts 189-90, Reg. Sess., An Act. . . Relative to the Sale and Possession of Machine Guns, No. 64, § 1 (vol. 115) - (:unkn) unknown (General Publisher, 1933)
Prohibited owning, possessing, and transporting a machine gun, light machine gun, or submachine gun without a permit. Punishable by imprisonment of 1-10 years.
--
Keywords: MACHINE GUN RESTRICTION